Reutilização de teste em linha de produtos de software baseado em máquina de estados finitos para sistemas embarcados - Capellari, Maykon Luís (2011)
Software Product Line (PL) is a recent approach which offers several benefits for organizations, such as significant reductions in development and maintenance costs and reduced time-to-market. The testing process cannot always follow the development speed of a PL. Its relative cost becomes higher compared to the testing traditional systems. Thus, tests consume a lot of time and effort usually represents more than half the cost of developing single systems. There are various testing approaches that support the management and reuse of tests in PL. However, they do not promote the reuse of tests, and their results, among the products instantiated from a PL. Thus, this project proposes the development of an incremental test strategy based on Finite State Machines (FSM), this allows the reuse of tests between products instantiated from a PL. This reuse includes test process, artifacts and results already carried out. Aiming to analyze the feasibility of the proposed strategy two experiments were conducted, in both cases the strategy proved very effective in generating and reuse of testing among the products of PL.